Reduced histone methylation associated with elevated body-mass index influences host susceptibility to severe dengue - Lee, Ariel Jia Ni (Nanyang Technological University, 2021)
Dengue virus infection causes dengue fever (DF), a mild febrile illness, that in some cases progresses into severe dengue (SD), a life-threatening complication. Accumulating evidence supports obesity as a risk factor for SD, but molecular events that lead to SD outcome remain unknown. Hence, to glean insights into the early events involved, we explored early host responses post-infection with the closely related yellow fever vaccine strain (YF-17D), of which ~50% of subjects experienced a febrile illness comparable to DF at ~6 days post-infection. We tracked transcriptomic changes at day 0, 1 and 3 and identified a downregulation of KMT2 histone methyltransferases in high body-mass index (BMI), but not low BMI subjects at day 3 post-infection. Notably, this finding is consistent with a previous study showing that KMT2 transcripts are reduced in SD compared to DF during the early phase of the disease. The impact of KMT2 genes on viral replication was investigated using the drug, MM102, which reduced H3K4me1 in moDCs. Reduction of H3K4me1 levels resulted in suppression of inflammatory responses that promoted viral replication in moDCs. Overall, our findings show that reduction of KMT2 genes in high BMI subjects elevates the risk of SD by promoting viral infection during the pre-symptomatic phase of infection.